Caleb, Son of Jephunneh - As an Example of Fidelity to God. An Exegetical Study of Sir 46:7-10 - Pudełko, Judyta (The Biblical Annals, 2021)
Caleb is a secondary character in several episodes of the Exodus as well as the conquest of the Promised Land (Numbers 13–14; Josh 14:6-14). Praise of the Ancestors (Syr 44–49) contains a presentation of the biblical history of ancient Israel as the history of the covenant and a place of God’s intervention. Sirach presents, according to his own criteria, the most relevant and positive characters of this history. Caleb in Sirach’s description (46:7-10) is a faithful scout, who, together with Joshua, in the face of the rebellion of the Israelites, bears witness to an exemplary trust in God and encourages the Israelites to follow his lead. His courage and faithfulness are rewarded by receiving an inheritance of the piece of land in the Promised Land, which then becomes the property of his offspring. In the brief account of Sirach, Caleb has become a timeless example of the wise man – a sage who lives according to the word of God and encourages others to take up this challenge.